La victima en la justicia transicional (2018)
This paper is focused on talking deeply about the Victims in the Transitional Justice, in the general content as per each one of the laws that are a result of the peace treats in Colombia. As the problem statement, the following question is formulated: Have the rights of the victims really been materialized in the Transitional Law? The challenge to develop this work is to find that this laws are repairing the victims of the armed conflict